1972
DOI: 10.1021/j100667a029
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation of salts of thianthrene radical cations

Abstract: transition would be of the "normal" helix-to-coil variety, and hence increasing inert diluent concentration would increase Te.) Whether such a maximum can actually be observed within the accessible temperature and solute solubility range, however, would depend on the thermodynamic parameters for the particular system under investigation.In terms of the overall transition parameters, AHvh and Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 0 publications
2
18
0
Order By: Relevance
“…The corresponding values of thianthrene were Eeal -Epa2 x 0.20 V; -A&, = 19.3 kJ/ mol; Kdim%l.l-10 at 256 K and 0.3 V; 28.9 kJ/mol; Kdim%4.IO6 at 233 K respectively. In the case of thianthrene, the order of magnitude of KDim is in good agreement with the spectroscopic results (UV-VIS) by de Sorgo et al [6] after converting the equilibrium constants of the latter investigation into those of a pure dimerization 2 T+' = TP. An estimation of the kinetic parameters of the reversible dimerization (TMOT) with the aid of digital simulations [17] yielded values of kf x 1.10' and k b x l.2.104.…”
Section: Methodssupporting
confidence: 87%
See 2 more Smart Citations
“…The corresponding values of thianthrene were Eeal -Epa2 x 0.20 V; -A&, = 19.3 kJ/ mol; Kdim%l.l-10 at 256 K and 0.3 V; 28.9 kJ/mol; Kdim%4.IO6 at 233 K respectively. In the case of thianthrene, the order of magnitude of KDim is in good agreement with the spectroscopic results (UV-VIS) by de Sorgo et al [6] after converting the equilibrium constants of the latter investigation into those of a pure dimerization 2 T+' = TP. An estimation of the kinetic parameters of the reversible dimerization (TMOT) with the aid of digital simulations [17] yielded values of kf x 1.10' and k b x l.2.104.…”
Section: Methodssupporting
confidence: 87%
“…Its "thermodynamic" redox potentials are tabulated in the literature [5]. However, a few nonelectrochemical investigations, such as a study of visible absorption and ESR spectra of T/T+' [6] and a X-ray analysis of TMOT+'-salts [7], indicate that the radical cations T+' and T M O Y dimerize in solution. Thus, at low temperatures and high concentrations of T+' new absorption bands at 1=470 and 594 nm were observed which were attributed to a dimer with a sandwich-like structure [6,71.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the bands around 370 and 690 nm are absent in dichloromethane solution spectra (Figure 1c). The presence of dimeric species in acetonitrile but not in dichloromethane might be attributed to the neutralization of repulsive forces 17. EPR spectra of salts BZ .…”
Section: Resultsmentioning
confidence: 99%
“…3.2Å [95]. Solution studies of 18b +• by UV-vis spectroscopy showed the presence of monomer-dimer equilibrium [96,97]. A number of structurally characterized derivatives of 1,4-dithiin 18a +• radical cation is much more limited, with one example of dimer [98] and monomer [99] reported so far.…”
Section: 4-dithiinium Radical Cationmentioning
confidence: 99%